Novel and Investigational Treatments for Onychomycosis - Stamatios Gregoriou; Maria Kyriazopoulou; Aikaterini Tsiogka; Dimitrios Rigopoulos (Journal of Fungi, 2022)
Onychomycosis is a common nail disease caused by fungi. The primary pathogens are dermatophytes; however, yeasts, non-dermatophyte moulds, and mixed fungal populations may also contribute to the development of a recalcitrant condition, usually accompanied by difficulties in everyday life and severe emotional stress. Treatment failure and relapse of the infection are the most frequent problems, though new issues have become the new challenges in the therapeutic approach to onychomycosis. Resistance to antifungals, an increasing number of comorbidities, and polydrug use among the ageing population are imperatives that impose a shift to safer drugs. Topical antifungals are considered less toxic and minimally interact with other drugs. The development of new topical drugs for onychomycosis is driven by the unmet need for effective agents with prolonged post-treatment disease-free time and a lack of systemic impact on the patients’ health. Efinaconazole, Tavaborole, and Luliconazole have been added to physicians’ weaponry during the last decade, though launched on the market of a limited number of countries. The pipeline is either developing new products (e.g., ME-1111 and NP213) with an appealing combination of pharmacokinetic, efficacy, and safety properties or reformulating old, well-known drugs (Terbinafine and Amphotericin B) by using new excipients as penetration enhancers.